PENERRAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 030 SIBUAK - Uub Mahbub; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the problem of this research is students lower score in learning sciences  Of class IV SDN 030 Sibuak, it can be seen from 20 students of class IV, 12 student (60%) got lower score and 8 students (40%) got higher score with the mean score is 65,57, the KKM of this school is 70. According to the problem, the researcherhas conducted a classroom action research by implementing assurance, Cooperative model. In cycle I, the percentage of teacher’s activity in first meeting is adequate 66,7 %. In the second meeting, it increasedto 79,1% with good category, in cycle II, first meeting it increased to 83,3% with good category in first meeting and second meeting indicated in very good category 87,5%. In cycle I, the percentge of student’s activity in first meeting is adequate 62,5%. In the second meeting, it increased to 75% with good category. In cycle II, first meeting it increased to 83,3% with category in first meeting and second meeting indicated in very good category 87,5%. An average score of student’s learning result before implementation Cooperative  model was 65,57 it increase to 67,5 in cycle I, and 85,0 in cycle II. The classical completeness was achieved in both cycle. In conclusion, the implementation Cooperative model can improve student’s learning result in sciences subject of class IV of  SDN  030 Sibuak Key Words: Cooperative model, Lerning Result Of Sciences Subject